2008
DOI: 10.1128/ec.00413-07
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signals in the Trafficking of Toxoplasma gondii Protein MIC3 to the Micronemes

Abstract: The protozoan parasite Toxoplasma gondii is equipped with a sophisticated secretory apparatus, including three distinct exocytic organelles, named micronemes, rhoptries, and dense granules. We have dissected the requirements for targeting the microneme protein MIC3, a key component of T. gondii infection. We have shown that MIC3 is processed in a post-Golgi compartment and that the MIC3 propeptide and epidermal growth factor (EGF) modules contain microneme-targeting information. The minimal requirement for mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 36 publications
4
47
1
1
Order By: Relevance
“…Here we have demonstrated that NcMIC2-like1 is mainly located in the apical region of the tachyzoite, possibly in the micronemes, such as demonstrated for NcMIC2 (Lovett et al 2000), TgMIC2 , TgMIC 3 (El-Hajj et al 2008) and NcAMA 1 (Zhang et al 2006). To corroborate with microneme localization, the secretion of NcMIC2-like1 was dependent on intracellular Ca 2 + .…”
Section: Discussionsupporting
confidence: 71%
“…Here we have demonstrated that NcMIC2-like1 is mainly located in the apical region of the tachyzoite, possibly in the micronemes, such as demonstrated for NcMIC2 (Lovett et al 2000), TgMIC2 , TgMIC 3 (El-Hajj et al 2008) and NcAMA 1 (Zhang et al 2006). To corroborate with microneme localization, the secretion of NcMIC2-like1 was dependent on intracellular Ca 2 + .…”
Section: Discussionsupporting
confidence: 71%
“…Here, we provide evidence that proteins from the tachyzoite secretory organelles, rhoptries and dense granules are heparin-binding lectins. Interestingly, microneme proteins, which are considered to be a major class of T. gondii cellular adhesins (Barragan et al 2005;Carruthers and Tomley 2008;El Hajj et al 2008;Soldati-Favre 2008), were not identified by heparin affinity chromatography, confirming that these proteins have an affinity for sialic acid-containing cell surface molecules. Indeed, the heparin-and sialic acid-based invasion pathways were thought to be simultaneously accessible and independent.…”
Section: Discussionmentioning
confidence: 84%
“…All these events lead to the creation of the parasitophorous vacuole within the host cell, in which parasites undergo rapid multiplication (Carruthers and Boothroyd 2007;Plattner and Soldati-Favre 2008;Soldati-Favre 2008;Blader and Saeij 2009). Microneme proteins and their proteolytic trimming fragments are considered to be a major class of cellular adhesins involved in recognition and attachment to host cells Cérède et al 2002;Barragan et al 2005;Carruthers and Tomley 2008;El Hajj et al 2008;Soldati-Favre 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However toxoplasmosis can be harmful in pregnant women and in immuncompromised individuals. Invasion by this parasite involves a large number of proteins such as MIC1-MIC12, RON1-RON5, GRA1-GRA8, which have been characterised using proteomics and genomics methods [2]. Some of these proteins have been used as diagnostic markers and all of them were identified by employing either T. gondii grown in cell culture (in-vitro) or in animals (in-vivo) [3].…”
Section: Introductionmentioning
confidence: 99%